Strengthening the Role of Islamic Philanthropy in Promoting Humanitarian Sustainability: A Study in Indonesia and Denmark - Runtiningsih, Sri; Jayanto, Prabowo Yudo; Asrori; Putra, Maulana Kurnia; Asif, Rukhsar (Universitas Negeri Semarang, 2025)
This community service initiative was implemented through the International Community Service (ICS) 2025 under the theme